A stenography application for hiding student information into an image - Yigit, Yildiray; Karabatak, Murat (Institute of Electrical and Electronics Engineers Inc., 2019)
Information security is a major problem today. Different approaches and methods are introduced every day for data protection. One of them is steganography. The word steganography combines the Greek words steganos (Greek passage), meaning "covered, concealed, or protected," and graphein (Greek passage) meaning "writing". The purpose of steganography is to construct the stego object by placing important information invisible into the ordinary cover object (image, sound, video, text, etc.) and to transmit it to the recipient. In this study, it is aimed to strengthen the LSB technique which is one of the steganography methods by suggesting the use of mask which will provide the least change on the image while hiding the data into a digital image. In the proposed method, the data is also compressed by the LZW algorithm, thus allowing more data to be hidden. © 2019 IEEE.
7th International Symposium on Digital Forensics and Security, ISDFS 2019 -- 10 June 2019 through 12 June 2019 -- Barcelos -- 149395
Keywords: Compression; Data security; Image; LSB; LZW; Steganography